Examining Illocutionary Acts: Male and Female Judges’ Comments on Indonesia’s Next Top Model - Zalikha; Dian Budiarti (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2024)
This article delves into the linguistic and discursive aspects of communication, exploring the application of theories proposed by J.L. Austin (1975) and John Searle (1969) to understand the illocutionary acts employed by the male and female judges in Indonesia's Next Top Model. Within the context of reality television, where judgments and critiques are integral components, the language used by judges holds particular significance. This study aims to delve into the illocutionary acts employed by male and female judges in the popular television show